2014
DOI: 10.1016/j.msea.2014.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Multi scale modeling and characterization of inelastic deformation mechanisms in continuous fiber and 2D woven fabric reinforced metal matrix composites

Abstract: Continuous unidirectional ceramic fiber and woven fabric reinforced metal matrix composites (MMCs) have potential to obtain very high specific strengths and stiffnesses, but use in structural applications has thus far been limited by their inherently low ductility, particularly in tensile loading conditions. In this work, a multi-scale micromechanics based finite element framework is used to predict, and understand the effect of microstructure on the tensile deformation behavior, including progressive damage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…The 3D weave material had the lowest V BL 50 which was 13% lower than the 0/90 materials. All four MMCs exhibited generally brittle behavior with damage dominated by their inherently low in-plane tensile elongation [8]. All impacts that completely penetrated the panels created smooth entrance holes roughly the same diameter as the FSP, and varying degrees of spall on the exit holes as shown in Fig.…”
Section: Ballistic Impact Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The 3D weave material had the lowest V BL 50 which was 13% lower than the 0/90 materials. All four MMCs exhibited generally brittle behavior with damage dominated by their inherently low in-plane tensile elongation [8]. All impacts that completely penetrated the panels created smooth entrance holes roughly the same diameter as the FSP, and varying degrees of spall on the exit holes as shown in Fig.…”
Section: Ballistic Impact Resultsmentioning
confidence: 93%
“…The density (r) of the MMC was 3.2 g/cm 3 . The in-plane elastic modulus (E 11 ¼ E 22 ), initial yield strength (s y ), ultimate tensile strength (s t u ), and tensile failure strain (ε t f ) of the MMC were 139 GPa, 52.5 MPa, 326 MPa, and 0.0041 respectively [8]. The through thickness (normal to plane of fabric weave) modulus (E 33 ) and compressive strength (s c u ) were found to be 120 GPa and 377 MPa respectively from quasi-static compression testing using ASTM standards [31].…”
Section: Model Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…In our micro-scale model, fibres were arranged hexagonally considering high-fibre volume fractions in fibre bundles of braided composites. Previous studies [29,30] demonstrated that predictions of elastic moduli and strengths based on hexagonal and random arrangements were very similar Specifically, this volume fraction was assumed as 0.8 herein with a representative unit cell (RUC) as depicted in Fig. 1, in which 2pr 2 /ab = 0.8.…”
Section: Multi-scale Modelling Approach Geometric Representative Unitmentioning
confidence: 99%